Analisis Perencanaan Pembiayaan Pendidikan di Tingkat Sekolah Menengah Pertama - Rahmah, Aziza; Syafriani, Velly; Asmendri; Sari, Milya (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
The aim of this study is to examine the planning used by UPTD SMP Negeri 2 Kecamatan Lareh Sago Halaban in education financing. This research employs a qualitative method with data collection techniques including interviews and documentation. The research was conducted at UPTD SMP Negeri 2 Kecamatan Lareh Sago Halaban. The study focuses on the education financing planning at the school, covering the grouping, classification, and utilization of education funds sourced from the Central Government (BOS funds), the Local Government, and contributions from students' parents managed by the school committee. Financing is divided into direct costs (related to the education process), routine costs (using BOS funds), and indirect costs (funded by parental contributions). The RAPBS preparation strategy begins with identifying the funding sources, gathering needs proposals from the school community, drafting by the treasurer and BOS team, followed by meetings with the school committee for revisions and the final approval of the RAPBS. In conclusion, the education financing planning at this school is well-structured; however, it is recommended to enhance transparency and the participation of the school committee in every stage of the RAPBS preparation